"Watchful Waiting" Advice for Pediatric Ear Infections. (June 2020) - MacGeorge, Erina L.; Foley, Kasey A.; Firgens, Emily P. C.; Vanderbilt, Rachel R.; Worthington, Amber K.; Hackman, Nicole M.
To reduce antibiotic use, clinical guidelines recommend treating many pediatric ear infections with watchful waiting (WW), which entails parents managing children's symptoms while waiting to see if the infection will resolve without antibiotics. This study examines providers' WW advice in recorded medical visits ( n = 28), focusing on five communication elements specified by guidelines and consistent with advice response theory. Results suggest directions for improving providers' delivery of WW advice and are discussed with regard to theory.